The role of teaching quality, online course design, and prompt feedback in shaping student expectations and academic performance in the Klang Valley - Zainal Abidin, Mohamad Imaduddin; Rochin Demong, Nur Atiqah (Universiti Teknologi Mara Selangor, 2025)
Due to Corona Virus (Covid-19) outbreaks, there has been a massive change in our education system. The education system has been influenced by Covid-19 and has led to worldwide closures. The whole world has taken this action to prevent coronavirus transmission among students. In response to this action, the education system, especially in Malaysia, has shifted to open distance learning, e-learning. Classes has been conducted via online platform and tremendous changed from traditional to digital. This change is one of the challenges in Malaysia's education system, from junior to higher learning levels. Despite the increase in open distance learning or online classes in higher institutions, this study tends to identify which factor during open distance learning or online classes could lead to students’ academic performance. This paper has identified the relationship between quality of lecturer, course design, lecturer's prompt feedback, and student expectations on student’s academic performance among university students in Klang Valley area. The study was quantitative, therefore, the data has been collected from selected higher institutions via an online survey. The sample for this study consists of higher learning students in selected higher institutions in the Klang Valley area with the total of 200 respondents to assess relationship between impact of open distance learning and student’s academic performance. Data were quantitatively analyzed using regression technique via SPSS. The result demonstrates a significant relationship between quality of lecturer, lecturer's prompt feedback, and student expectations on student’s academic performance. However, course design variables show a negative relationship towards student’s academic performance. Hence, this study confirmed all variables are significantly related to student’s academic performance among university students in Klang Valley.